Emerging advances in identifying signal transmission molecules involved in the interaction between Mycobacterium tuberculosis and the host - Wang, Yue; Shi, Qiyuan; Chen, Qi; Zhou, Xuebin; Yuan, Huiling; Jia, Xiwen; Liu, Shuyuan; Li, Qin; Ge, Lijun (Frontiers in Cellular and Infection Microbiology, 2022)
Tuberculosis caused by Mycobacterium tuberculosis (MTB) is an ancient chronic infectious disease and is still the leading cause of death worldwide due to a single infectious disease. MTB can achieve immune escape by interacting with host cells through its special cell structure and secreting a variety of effector proteins. Innate immunity-related pattern recognition receptors (PPR receptors) play a key role in the regulation of signaling pathways. In this review, we focus on the latest research progress on related signal transduction molecules in the interaction between MTB and the host. In addition, we provide new research ideas for the development of new anti-tuberculosis drug targets and lead compounds and provide an overview of information useful for approaching future tuberculosis host-oriented treatment research approaches and strategies, which has crucial scientific guiding significance and research value.